Shohojogi: an automated Bengali voice chat system for the banking customer services - Arnab, Kabir Abdur Rahman; Hossain, Md Ashiqual; Nabi, Istihad; Shoyti, Sadia Afrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.